Hubungan Kualitas Tidur terhadap Produktivitas Kerja Driver Goseh Tanah Karo - Cahyani Arifah; Reni Agustina Harahap; Yulia Khairina Ashar; Tri Niswati Utami; Adenan Adenan (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
The flexible work system for online motorcycle taxi drivers can lead to irregular working hours and rest periods, potentially reducing sleep quality and work productivity. This study aims to determine the relationship between sleep quality and work productivity among online motorcycle taxi drivers in Goseh Tanah Karo. This study used a quantitative analytical design with a cross-sectional approach. A sample of 75 respondents was selected using a purposive sampling technique. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and work productivity questionnaires, then analyzed using the Chi-square test. The results showed that 78.7% of respondents had poor sleep quality and 60% had low work productivity. There was a relationship between sleep quality and work productivity (p=0.038) with a prevalence ratio (PR) of 1.763. Drivers with poor sleep quality had a prevalence of low work productivity 1.763 times greater than drivers with good sleep quality. It was concluded that sleep quality is related to work productivity among online motorcycle taxi drivers in Goseh Tanah Karo.